The Economics of Network Reconfiguration and Shunt Compensation on a 33 kV Distribution Network - Lawal, Muyideen; Olawuyi, Abdulsemiu; Awomolo, Kayode; Jimoh, Abdulrasaq (Journal of Science and Technology, 2023)
This work studies the cost benefits derivable from network reconfiguration and shunt compensation of a Nigerian 33 kV distribution network. The approach adopted requires that the base case power flow analysis of the distribution network was first carried out, after which a shunt capacitor was used for compensation. The introduction of a tie-line in the network and a combination of capacitor and tie-line on same network were also carried out. The costs analysis of compensation and reconfiguration was carried out to understand their financial worthiness. The results obtained showed that the payback period (PP) for the introduction of compensation only, reconfiguration only and combination of compensation and reconfiguration are 1286.89 hr, 328.58 hr and 1043.31 hr, respectively. Though, reconfiguration only gives the least PP, a combination of compensation and reconfiguration has a long time cost benefit. At time above 5147.57 hr, it generates more profit than others.